Biased Survival Expectations and Behaviours: Does Domain Specific Information Matter? - Joan Costa-Font; Cristina Vilaplana-Prieto (Institute of Labor Economics (IZA), 2021)
We study biased survival expectations across two domains and examine whether such biased expectations influence health and financial behaviors. Combining individual-level longitudinal data, retrospective, and end of life data from several European countries for more than a decade, we estimate time-varying individual level bias in 'survival expectations' (BSE) at the individual level and compare it to biased 'meteorological expectations' (BME). We exploit variation in an individual's family history (parental age at death) to estimate the effect of BSE on health and financial behaviors and compare it to BME, and other tests to discuss whether the effect of BSE results from the effect of private information. We find that BSE increases the probability of adopting less risky behaviors and financial behaviors. We estimate that a one standard deviation increase in BSE reduces the average probability of smoking by 48% and holding retirement accounts by 69%. In contrast, BME barely affects healthy behaviors, and is only associated with a change in some financial behaviors.
Keywords: I18; D14; G22; 330; financial behaviour; health behaviour; biased expectations; survival expectations; meteorological expectations; longevity optimism; private information